Peran Kepercayaan terhadap Pemerintah dalam Memoderasi Pengaruh Kesadaran Wajib Pajak dan Kualitas Pelayanan Fiskus terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus di KPP Pratama Depok Sawangan) - Paras Yustiani; Dani Rahman Hakim (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to determine the influence of taxpayer awareness and the quality of tax authority services on individual taxpayer compliance, with trust in the government serving as a moderating variable. This study employs a quantitative research design and utilizes primary data. The study population consists of all individual taxpayers registered at the KPP Pratama Depok Sawangan tax office. Based on the Slovin formula with a 10% margin of error, the minimum sample size required was 100 respondents; however, data from 118 respondents were successfully collected and processed using the incidental sampling technique. Data collection was conducted via questionnaires. The data analysis technique employed was Partial Least Squares-based Structural Equation Modeling (SEM-PLS), utilizing SmartPLS version 4 software. The results indicate that taxpayer awareness and the quality of tax authority services have a direct, positive, and significant influence on individual taxpayer compliance. Furthermore, trust in the government moderates and strengthens the influence of the quality of tax authority services on individual taxpayer compliance.